2021
DOI: 10.3390/electronics10202471
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Supervised Machine Condition Monitoring by Learning Deep Discriminative Audio Features

Abstract: In this study, we aim to learn highly descriptive representations for a wide set of machinery sounds and exploit this knowledge to perform condition monitoring of mechanical equipment. We propose a comprehensive feature learning approach that operates on raw audio, by supervising the formation of salient audio embeddings in latent states of a deep temporal convolutional neural network. By fusing the supervised feature learning approach with an unsupervised deep one-class neural network, we are able to model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This illustrates that the proposed model significantly outperforms all existing models for both tested machines (i.e., pumps and valves). The malfunction detection in terms of the performance of an AUC increases by up to 9.51% and 3.23% for the pumps and valves, respectively, compared to the newest model developed this year by Thoidis et al [41]. This improvement is also supported by the F1 value of pumps compared to a previous model that increased malfunction detection by 9.56%.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This illustrates that the proposed model significantly outperforms all existing models for both tested machines (i.e., pumps and valves). The malfunction detection in terms of the performance of an AUC increases by up to 9.51% and 3.23% for the pumps and valves, respectively, compared to the newest model developed this year by Thoidis et al [41]. This improvement is also supported by the F1 value of pumps compared to a previous model that increased malfunction detection by 9.56%.…”
Section: Discussionmentioning
confidence: 69%
“…In this experiment, it is shown that the proposed model is effective with both pump and valve machine types due to balanced AUC between pumps and valves (less than 1%), while other existing models, such as SPIDERnet, AE by Purohit et al [19], and MDF-FCN, are more suited for pumps than valves. Talmoudi and Hirata [42], Ribeiro et al [6] and RawdNet by Thoidis et al [41] are more suited for valves. These are shown due to their performance of an AUC that differs from 3.7% up to 21.5% for pumps compared to valves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using semi-supervised, unsupervised, and self-supervised learning methods include outlier detection, using self-supervised complex networks [12], outlier detection, using an unsupervised domain adaptation method [13], a study on a learning MIMII dataset through the semi-supervised learning of the RawdNet model [14], and an outlier detection study using self-supervised learning that utilizes a contrast learning framework [15]. MIMII dataset preprocessing has been realized by removing noise from MIMII datasets, via NMF and nnCP models [16].…”
Section: Related Workmentioning
confidence: 99%